Sustaining affirmation : the strengths of weak ontology in political theory - White, Stephen K. (Princeton University Press, 2000)
In light of many recent critiques of Western modernity and its conceptual foundations, the problem of adequately justifying our most basic moral and political values looms large. Without recourse to traditional ontological or metaphysical foundations, how can one affirm--or sustain--a commitment to fundamentals? The answer, according to Stephen White, lies in a turn to "weak" ontology, an approach that allows for ultimate commitments but at the same time acknowledges their historical, contestable character. This turn, White suggests, is already underway. His book traces its emergence in a variety of quarters in political thought today and offers a clear and compelling account of what this might mean for our late modern self-understanding. As he elaborates the idea of weak ontology and the broad criteria behind it, White shows how these are already at work in the thought of contemporary writers of seemingly very different perspectives: George Kateb, Judith Butler, Charles Taylor, and William Connolly